Peran Guru dalam Pembentukan Karakter Anak Kelas B di TK Kartini Biyonga Kecamatan Limboto Kabupaten Gorontalo - Miftahu Rizki R. Piko; Nurhayati Tine; Nunung Suryana Jamin (Jurnal Pendidikan dan Sastra Inggris, 2025)
This research is motivated by the importance of the role of teachers in the process of personality formation of early childhood, particularly in Kartini Biyonga Kindergarten. The purpose of this study is to identify the role of teachers in the formation of children's personalities and describe the methods used by teachers in the formation of children's characters in the school environment. This study uses a qualitative approach with descriptive methods. Data were collected through observation, interviews, and documentation techniques, while teachers act as the main participants in this study. The results show that teachers have a central role as role models, guides, and motivators for children in the process of forming positive behavior. Kartini Biyonga Kindergarten teachers play an active role in providing continuous guidance, training, and advice to students. In shaping children's characters, teachers use habituation strategies through activities such as talking, playing, and interacting through positive things that can be imitated and applied in everyday life. Through this approach, children learn to imitate good behavior and internalize moral values ​​naturally. This finding confirms that the role of teachers is very important in forming the foundation of personality and character of early childhood as a provision for their future development.